VD_FINDINFO HC / 2012 / 185 vom 7. März 2012 - VD Tribunal cantonal (2012)
AUDITION DE L'ENFANT, DROIT DE GARDE | 176 al. 3 CC, 107 al. 2 LTF, 276 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH), 317 al. 1 CPC (CH)